2021
DOI: 10.3389/fpsyg.2021.655796
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Sext-Sharing Among a Representative Sample of Youth in the Netherlands

Abstract: Many adolescents use their electronic devices to send each other sexually explicit texts, photos, and videos of themselves—commonly known as sexting. This can be fun and is not usually problematic. However, if the intended recipient decides to share these sexts with a broader audience, the consequences for the depicted can be detrimental. The purpose of this study was to investigate the prevalence of (non-consensual) sext-sharing among Dutch adolescents and explore the characteristics of those who do, to gain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 64 publications
1
8
0
1
Order By: Relevance
“…A study of six- to nine-year-old US students found that coercion to participate in cybersex or repeatedly requesting explicit images was perpetrated by 8% of a sample of 1,236 students aged 11–14 years, with the 14-year-old cohort over two and a half times more likely to engage than the 11-year-old participants (Smith-Darden et al , 2017). Similar results were seen in The Netherlands, with the 15–17 age group more likely to share sexts than the 12–14 age group (Boer et al , 2021). Harassment can also involve “sextortion”, sexual extortion, where the offender demands explicit content with threats to harm the victim if the demand is not met, often by making previously shared images public (Lee and Darcy, 2021).…”
Section: Digitally Assisted Crimesupporting
confidence: 76%
“…A study of six- to nine-year-old US students found that coercion to participate in cybersex or repeatedly requesting explicit images was perpetrated by 8% of a sample of 1,236 students aged 11–14 years, with the 14-year-old cohort over two and a half times more likely to engage than the 11-year-old participants (Smith-Darden et al , 2017). Similar results were seen in The Netherlands, with the 15–17 age group more likely to share sexts than the 12–14 age group (Boer et al , 2021). Harassment can also involve “sextortion”, sexual extortion, where the offender demands explicit content with threats to harm the victim if the demand is not met, often by making previously shared images public (Lee and Darcy, 2021).…”
Section: Digitally Assisted Crimesupporting
confidence: 76%
“…Since schools are places where children and adolescents first socialize and educate themselves, as well as develop online and offline relationships, moral behavior, and communication, there is a wide range of school-based interventions aimed at preventing online sexual violence, including the sharing of unwanted intimate sexual messages [ 97 ]. However, many of these programs merely focus on abstinence from sexting and the use of risk communication strategies to discourage sexting altogether, while no alternative digital sexual education interventions have been observed [ 98 , 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a research project with 357 adolescents, Symons et al (2018) point out the high probability that sexting will take place in the context of a romantic relationship. A study by Boer et al (2021) demonstrates different usages of sexting dependent on the gender and socio-economic status of the adolescents.…”
Section: Research On Image-based Sexual Communication Through Digital Media – Between Self-determination and Boundary Violationsmentioning
confidence: 99%